Acute coronary syndrome with elevation of ST associated with ergotamine abuse - Pérez Baztarrica Gabriel E.; Armijos Carrion Leonardo P.; Abarca Real Juan H.; Paredes Lima William A.; Giler Saltos Otto P.; Porcile Rafeal (Sciendo, 2019)
There are few case reports of cases of carotid and aortic dissection related to the ergotamine abuse, but the cases that affect the coronary arteries is a very rare coronary. We present a patient of a 48-year-old female with an ST-segment elevation myocardial infarction attributable to chronic ergotamine use. The coronary angiography showed dissection of right coronary artery proximal.